The mevalonate pathway regulates microRNA activity in Caenorhabditis elegans - Shi, Zhen (National Academy of Sciences, 2012)
The mevalonate pathway is highly conserved and mediates the production of isoprenoids, which feed into biosynthetic pathways for sterols, dolichol, ubiquinone, heme, isopentenyl adenine, and prenylated proteins. We found that in Caenorhabditis elegans, the nonsterol biosynthetic outputs of the mevalonate pathway are required for the activity of microRNAs (miRNAs) in silencing their target mRNAs. Inactivation of genes that mediate multiple steps of the mevalonate pathway causes derepression of several miRNA target genes, with no disruption of the miRNA levels, suggesting a role in miRNA-induced silencing complex activity. Dolichol phosphate, synthesized from the mevalonate pathway, functions as a lipid carrier of the oligosaccharide moiety destined for protein N-linked glycosylation. Inhibition of the dolichol pathway of protein N-glycosylation also causes derepression of miRNA target mRNAs. The proteins that mediate miRNA repression are therefore likely to be regulated by N-glycosylation. Conversely, drugs such as statins, which inhibit the mevalonate pathway, may compromise miRNA repression as well as the more commonly considered cholesterol biosynthesis.